Tritrichomonas Foetus: A Study of Prevalence in Animal Hosts in Poland - Dąbrowska, Joanna (Pathogens, 2020)
Tritrichomonas foetus is described as a pathogen of cattle and cats and also exhibits commensalism with pigs. In order to estimate the prevalence and determine the risk factors for parasite infection, specimens from animal hosts (cat, pigs, and cattle) from Poland were investigated. To our best knowledge, this is the first such study to examine samples from wild boars (Sus scrofa) for the presence of T. foetus. Data were collected from 117 cats, 172 pigs, 236 wild boars, and 180 cattle. The sensitivity of T. foetus identification was increased by using two molecular assays: PCR and loop-mediated isothermal amplification (LAMP). The prevalence of feline tritrichomonosis was 20.51%, and statistically significant differences were obtained between groups of animals regarding age, breed, number of cats, diarrhea, and place of living. Positive PCR and LAMP results for T. foetus were estimated for 16.28% of pigs, and the obtained data were significantly correlated with age. Conversely, no significant differences were observed concerning the farm size factor. In our survey, no cases of bovine tritrichomonosis were found, which is consistent with the data from the other countries of the European Union. Similarly, all wild boar samples were also T. foetus-negative according to LAMP and PCR.